Guest

Functions f , g : R → R are defined, respectively, by f (x) = x2 + 3x + 1, g (x) = 2x – 3, find g o f

 Functions f , g : R → R are defined, respectively, by f (x) = x2 + 3x + 1, g (x) = 2x – 3,
find  g o f  

Grade:12

1 Answers

Roshan bist
15 Points
one year ago
Gof(X)=g(f(X)=g(x^2+3x+1)=2(x^2+3x+1)-3=4x^2+6x+2-3=4x2+6x-1 is the answer of questions no q. how to take online courses I am from Nepal

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free